Local multiplicity fluctuations in hadronic Z decay - Dova, María Teresa (1998)
Local multiplicity fluctuations in hadronic Z decays are studied using the L3 detector at LEP. Bunching parameters are used for the first time in addition to the normalised factorial moment method. The bunching parameters directly demonstrate that the fluctuations in rapidity are multifractal. Monte Carlo models show agreement with the data, reproducing the trend, although not always the magnitude, of the factorial moments and bunching parameters.